Tachiramantis lassoalcalai (Barrio-Amorós, Rojas-Runjaic & Barros, 2010) (Anura, Craugastoridae): a new combination revealed by molecular evidence, with a description of its advertisement call - Rojas-Runjaic, Fernando J. M.; Echevarría, Lourdes Y.; Becerra-Rondón, Adriana C.; Infante-Rivero, Edwin E. (Zootaxa, 2020)
Pristimantis lassoalcalai Barrio-Amorós, Rojas-Runjaic & Barros, 2010 is a poorly known terrarana, endemic to the eastern slope of Sierra de Perijá in Venezuela. Although a close relationship of this species with Tachiramantis has been suspected based on its overall morphological similarity, this relationship had not been tested so far. On the basis of molecular data (two fragments of the 12S and 16S mtDNA genes) obtained from the type series, we reconstruct its evolutionary relationships and establish its phylogenetic position as a member of Tachiramantis. Based on this phylogenetic hypothesis, we transfer Pristimantis lassoalcalai to Tachiramantis as Tachiramantis lassoalcalai comb. nov. In addition, we describe its advertisement call. This is the fourth known species of the genus and the second to which its vocalization is described.